What drives youths to vote?: An analysis of politico-behavioural constructs in Southwestern Nigeria - Timilehin Olayinka Omoniyi (Goodwood Publishing, 2025)
Purpose: This study aims at investigating how partisan alignment, geopolitical affiliation, issue-based orientation, monetary inducement, and behavioural persuasion influence voting behaviour among Nigerian youth aged 18–35 in a transitional democracy context. Methodology/approach: A descriptive survey design of correlational type was adopted, using a validated structured questionnaire (six sections; reliability range r = 0.85–0.91). A stratified sample of 1,500 registered youth voters was drawn across Ondo, Oyo, and Osun States. Data were analysed with SPSS version 25 using descriptive statistics, Pearson correlation, and multiple regression at a 0.05 significance level. Results/findings: Positive significant relationships were found with partisan alignment (r = .206), geopolitical affiliation (r = .253), and behavioural persuasion (r = –.128). The composite model was significant (Adj. R² = .110). Only partisan alignment (? = .187), geopolitical affiliation (? = .256), and behavioural persuasion (? = –.081) were significant predictors. Conclusion: Youth voting behaviour in Southwestern Nigeria is shaped predominantly by partisan alignment, geopolitical affiliation, and behavioural persuasion, with issue-based orientation and monetary inducement showing no significant direct effect. These findings highlight the enduring influence of identity and persuasion in transitional democracies, despite growing discourse on issue-based politics. Limitations: The study was limited to Southwestern Nigeria and relied solely on quantitative self-reported data. Contribution: Findings are useful for political science, youth studies, electoral education, and governance policy, offering insights for strategies to enhance democratic participation and electoral integrity in transitional democracies.